Prinsip Etika dalam Bisnis dan Kewirausahaan Berbasis Islam - Evarianisa Endang Trisnani (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
Efforts to build a business ethics that creates an Islamic business framework require a reconstruction of a new awareness about the meaning of business. Business, whether run by individuals, organizations, or companies, should not only focus on worldly aspects but also encompass both material and spiritual dimensions. A business is considered valuable if it can meet physical and spiritual needs in a balanced way, without containing elements of falsehood, corruption, or injustice. In contrast, an Islamic business must be based on values of unity, balance, responsible freedom, truth, goodness, and honesty. These principles can serve as benchmarks to assess whether a business aligns with or contradicts business ethics. Therefore, a new approach is needed to study business and economics, one that integrates normative-ethical paradigms with empirical-inductive analysis, and is oriented towards exploring and developing the values contained in the Qur'an.